The archaeology of Byzantine Anatolia : from the end of late antiquity until the coming of the Turks - Niewöhner, Philipp (Oxford University Press, 2017)
Anatolia was the only major part of the Roman Empire that did not fall in late antiquity, but remained continuously under Roman rule through the eleventh century. Anatolia can, therefore, show the difference Roman administration continued to make, once pan-Mediterranean rule had collapsed. Urban decline did not set in before the fifth century, after Anatolia had already been thoroughly Christianized in the course of the fourth century. The urban decline, when it occurred from the fifth century onwards, was paired with rural prosperity, an increase in the number, size, and quality of rural settlements and in rural population. This work examines this topic